2014
DOI: 10.1159/000367832
|View full text |Cite
|
Sign up to set email alerts
|

New Drugs on the Horizon for IBD

Abstract: TNF antagonists have revolutionized the treatment of IBD. Nevertheless, between 30 and 45% of patients discontinue infliximab and other TNF antagonists over a 2- to 6-year period due to nonresponse, loss of response, or adverse events. Accordingly, the need for novel therapies grows each year. Recent studies have demonstrated the promise of new drugs with distinct modes of action for the treatment of ulcerative colitis (UC) and Crohn's disease (CD). These include agents targeting leukocyte trafficking, therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…The adverse effects were comparable between the vedolizumab group and placebo group in most studies. No cases of progressive multifocal leukoencephalopathy have been reported in previous studies [50][51][52][53][54].…”
Section: Vedolizumabmentioning
confidence: 87%
See 1 more Smart Citation
“…The adverse effects were comparable between the vedolizumab group and placebo group in most studies. No cases of progressive multifocal leukoencephalopathy have been reported in previous studies [50][51][52][53][54].…”
Section: Vedolizumabmentioning
confidence: 87%
“…For long-term efficacy, 41.8-44.8 % of patients who continued to receive vedolizumab every 8 weeks or every 4 weeks were in clinical remission at week 52, whereas only 15.9 % of patients who switched to placebo were in clinical remission at week 52 [50]. In the GEMINI I study, 44 % of patients had previously received an anti-TNF treatment, and this high percentage suggested that a highly refractory group of patients were included in this study [51]. However, the odds ratio for the clinical response of vedolizumab in compared to placebo was comparable between patients with prior anti-TNF treatment and patients without prior anti-TNF treatment.…”
Section: Vedolizumabmentioning
confidence: 95%
“…Patients with greater active UC levels treated with oral JAK inhibitor Tofacitinib have a higher effective and remission rate than those receiving the placebo [70]. Moreover, with the theoretical basis, PSC as an untypical autoimmune disease, may benefit from the treatment of Tofacitinib.…”
Section: Il-2/il-21/il-2rmentioning
confidence: 99%
“…Обнадеживающие результаты были получены в исследо-ваниях по изучению эффективности и безопасности пре-паратов, влияющих на миграцию лейкоцитов, антагони-стов интерлейкина 12, интерлейкина 23 и янус-киназы, а также антител к интерлейкину 6. Каждый из перечислен-ных выше препаратов обладает как рядом преимуществ, так и рядом ограничений к применению, в связи с чем требуются дальнейшие исследования в этой области [48]. Кроме того, возможность применения у пациентов с ВЗК таких препаратов, как пробиотики, молекулы, восстанав-ливающие экспрессию белков, формирующих плотные контакты или их синтетические аналоги, синтетические аналоги антимикробных пептидов, и соединения, обе-спечивающие дифференцировку макрофагов в заданном направлении, также подлежит обсуждению [40].…”
Section: рис 11 болезнь кронаunclassified